2015
DOI: 10.3109/02699052.2015.1031699
|View full text |Cite
|
Sign up to set email alerts
|

Mild traumatic brain injuries in early adolescent rugby players: Long-term neurocognitive and academic outcomes

Abstract: Tentatively, the outcome suggests cognitive vulnerability in association with school level participation in rugby.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 53 publications
1
34
0
Order By: Relevance
“…These figures are higher than most previous reports in youth rugby 15. Young athletes are more vulnerable to concussion and may be affected by more complicated recovery times and higher risk of adverse outcomes 11 12. In addition to the potential of acute catastrophic traumatic brain injury, there have been increasing concerns of potential long-term adverse effects of sports-related concussion particularly when multiple concussive blows are sustained over a lifetime 17–19.…”
Section: Concussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These figures are higher than most previous reports in youth rugby 15. Young athletes are more vulnerable to concussion and may be affected by more complicated recovery times and higher risk of adverse outcomes 11 12. In addition to the potential of acute catastrophic traumatic brain injury, there have been increasing concerns of potential long-term adverse effects of sports-related concussion particularly when multiple concussive blows are sustained over a lifetime 17–19.…”
Section: Concussionmentioning
confidence: 87%
“…Concussion can have devastating outcomes if not identified or managed accordingly. This is particularly pertinent in adolescent and young athletes, as developing brains undergo a more complex and protracted recovery postconcussion in comparison to an adult 11 12…”
Section: Introductionmentioning
confidence: 99%
“…Although Non Direct Head Impacts have been associated with concussion injuries [1, 23,24], this analysis is aimed at providing an evidence base for player actions which can help to decrease the risk of a Significant Direct Head Impact occurring. A particular focus is given to player stance, orientation and kinematics leading up to, and during, tackles.…”
Section: Takedownmentioning
confidence: 99%
“…The mechanics of acute injuries in rugby, for example concussion arising from direct head impacts, have been studied McIntosh, 2007, McIntosh et al, 2014). However, there is also mounting evidence of reduced long term cognitive ability in rugby players, even in those without a history of concussion (Alexander et al, 2015, Shuttleworth-Edwards and Radloff, 2008, Hume et al, 2016. This includes reduced visuomotor processing speeds (Shuttleworth-Edwards and Radloff, 2008) and short term visual memory (Alexander et al, 2015) in comparison to athletes from non-contact sport controls.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is also mounting evidence of reduced long term cognitive ability in rugby players, even in those without a history of concussion (Alexander et al, 2015, Shuttleworth-Edwards and Radloff, 2008, Hume et al, 2016. This includes reduced visuomotor processing speeds (Shuttleworth-Edwards and Radloff, 2008) and short term visual memory (Alexander et al, 2015) in comparison to athletes from non-contact sport controls. Furthermore, Hume et al (Hume et al, 2016) found that rugby players have longer reaction times, slower psychomotor speeds and reduced visual and verbal memory in comparison to age matched norms.…”
Section: Introductionmentioning
confidence: 99%